2006
DOI: 10.1638/05-065.1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Florfenicol After a Single Intramuscular Dose in White-Spotted Bamboo Sharks (Chiloscyllium Plagiosum)

Abstract: This study evaluated the pharmacokinetics of florfenicol in the white-spotted bamboo shark (Chiloscyllium plagiosum). In addition to the pharmacokinetics, the potential application for treatment of bacterial meningitis was explored. A pilot study was used to compare doses of 30, 40, and 50 mg/kg i.m. Following that study, 10 adult sharks were administered a single i.m. dose of florfenicol at 40 mg/kg. Plasma and cerebrospinal fluid were collected and analyzed for florfenicol by a sensitive and specific high-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The pharmacokinetics of FF has been reported in Atlantic salmon (Martinsen et al, 1993;Horsberg et al, 1994Horsberg et al, , 1996, red pacu (Lewbart et al, 2005), tilapia (Feng et al, 2008;Feng & Jia., 2009), cod (Hansen & Horsberg, 2000;Samuelsen et al, 2003), koi carp, and three spot gourami (Yanong & Curtis., 2005), Korean catfish (Park et al, 2006) and sharks (Zimmerman et al, 2006). The results showed that FF was absorbed rapidly, distributed extensively, and eliminated slowly.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The pharmacokinetics of FF has been reported in Atlantic salmon (Martinsen et al, 1993;Horsberg et al, 1994Horsberg et al, , 1996, red pacu (Lewbart et al, 2005), tilapia (Feng et al, 2008;Feng & Jia., 2009), cod (Hansen & Horsberg, 2000;Samuelsen et al, 2003), koi carp, and three spot gourami (Yanong & Curtis., 2005), Korean catfish (Park et al, 2006) and sharks (Zimmerman et al, 2006). The results showed that FF was absorbed rapidly, distributed extensively, and eliminated slowly.…”
Section: Introductionmentioning
confidence: 96%
“…, 2003), koi carp, and three spot gourami (Yanong & Curtis., 2005), Korean catfish (Park et al. , 2006) and sharks (Zimmerman et al. , 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacokinetic (PK) studies require frequent handling of the subjects for blood collection, making them less suitable for easily stressed, large or dangerous species ( 5 , 11 ). Very few PK studies have been carried out in elasmobranchs, and the ones performed used small benthic elasmobranch species such as the white bamboo shark ( Chiloscyllium plagiosum ) and the smooth dogfish ( Mustelus canis ) ( 12 , 13 ). An advantage of using elasmobranchs for the development of PK studies is that they are susceptible to tonic immobility (TI) ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…FFC is unresponsive to enzyme acetyltransferase that induces bacterial resistance to CAP, with FFC having a low risk of inducing aplastic anemia then it is exclusively design for complements the shortcomings of CAP (Dowling, 2013). A number of pharmacokinetic studies of FFC have been reported in aquatic animals, including Atlantic salmon (Horsberg et al, 1996), crucian carp (Yang et al, 2020), Nile tilapia (Rairat et al, 2019), pacu (Marques et al, 2018), and rainbow trout (Pourmolaie et al, 2015), common carp (Jangaran Nejad et al, 2017), rice field eel (Xie et al, 2013), snubnose pompano (Sumithra et al, 2023), and white-spotted bamboo sharks (Zimmerman et al, 2006), in mammalians, such as cattle (Lobell et al, 1994), dog (Birdane et al, 2015), goat (Verma et al, 2009), pig (Liu et al, 2003), and sheep (Shen et al, 2004), and in avian species, such as broiler chicken (Afifi & Abo el-Sooud, 1997), duck (Lan et al, 2019), geese (Tikhomirov et al, 2021), and turkey (Watteyn et al, 2018). However, there have been few reports on the pharmacokinetics and dosage regimen of FFC in reptiles, especially in sea turtles.…”
Section: Introductionmentioning
confidence: 99%